1976
DOI: 10.1007/bf00224305
|View full text |Cite
|
Sign up to set email alerts
|

The pit cell: Description of a new type of cell occurring in rat liver sinusoids and peripheral blood

Abstract: Pit cells--a new type of cell first described here and so named because they contain highly characteristic granules--are situated in the wall of rat liver sinusoids, and have hyaloplasmic pseudopodia intermingling with the microvilli of the parenchymal cells. The characteristic granules are mainly situated at one side of the nucleus, the other side showing organelle-free hyaloplasm. Pit cells are also found in portal tracts and in granuloma-like cellular aggregates. They also occur in rat peripheral blood, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
1
6

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(97 citation statements)
references
References 9 publications
2
88
1
6
Order By: Relevance
“…1 Pit cells, together with Kupffer cells, represent the first line of cellular defense against invading cancer cells in the liver. Pit cells were first described in 1976 by Wisse et al, 2 and their function as natural killer (NK) cells was suggested by Kaneda et al 3 They were first isolated by Bouwens et al, and their NK cell nature was ascertained. 4 Cytotoxicity experiments, using the 51 Cr release assay, against various tumor cell lines showed that pit cells are the most cytotoxic cells of the naturally occurring NK cells; their level of cytotoxicity is comparable with lymphokine-activated killer cells.…”
mentioning
confidence: 99%
“…1 Pit cells, together with Kupffer cells, represent the first line of cellular defense against invading cancer cells in the liver. Pit cells were first described in 1976 by Wisse et al, 2 and their function as natural killer (NK) cells was suggested by Kaneda et al 3 They were first isolated by Bouwens et al, and their NK cell nature was ascertained. 4 Cytotoxicity experiments, using the 51 Cr release assay, against various tumor cell lines showed that pit cells are the most cytotoxic cells of the naturally occurring NK cells; their level of cytotoxicity is comparable with lymphokine-activated killer cells.…”
mentioning
confidence: 99%
“…Pit cells are a unique population of cells occurring in rat buffered saline (PBS) supplemented with 0.1% ethylenediaminetetliver sinusoids, 1 and can be considered as natural killer (NK) raacetic acid, at a pressure of 50 cm H 2 O, and the perfusate was cells 2,3 with large granular lymphocyte (LGL) morphology. 4 collected through cannulation of the inferior vena cava.…”
mentioning
confidence: 99%
“…The data collected on the IL4 function raise the possibility that this cytokine (1) could be produced by liver-associated lymphocytes including large granular (i.e. Pit cells) and agranular lymphocytes [37,38], since these cells display natural killer and lymphokine-activated killer activities [38]; (2) could act on other hepatic functions (including plasma proteins and cytochrome P450 enzymes) and may antagonize and/or cooperate with other cytokines; (3) could be involved in the development of some liver diseases. Indeed, Schlaak et al [39] have recently reported elevated IL4 production by liver infiltrating T cells in autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 99%